Pengolahan Limbah Rumah Tangga Menjadi Pupuk Kompos Cair - Manu, Dolly Madya Parton; Ota , Muhammad; Hamid , Hayyu Ghani; Mawalif , Ihzar; Anugrah, Shuzan; Jusmadi, Evryeni; Nur’aini, Hesti; Fariadi, Herri (Universitas Dehasen Bengkulu, 2025)
This study examines the processing of household organic waste into liquid fertilizer in RT 08 RW 06 Betungan, Bengkulu, where the majority of the population migrated from South Bengkulu and work as farmers and daily laborers. With a population of around 875 people, the community in this area actively holds religious activities, religious studies, gymnastics, and weekly mutual cooperation, although awareness of household waste cleanliness still needs to be improved. The research method used is descriptive qualitative with a purposive sample of 15-20 households that process waste. Data were collected through interviews, observations, and documentation, then analyzed based on processing techniques, community participation, and fertilizer results. The results showed that processing organic waste into liquid fertilizer through fermentation with natural ingredients and EM4 microorganisms effectively reduces waste problems while increasing soil fertility and crop yields. This liquid fertilizer also reduces farmers' dependence on chemical fertilizers, making it more environmentally friendly and economical. This organic waste processing contributes to environmental sustainability and improving the welfare of the local community.